Protection of Models Due to Defaults in Agreements in the Modeling Industry - Wafa Az-Zahra; Tiara Sakinah Najat; Nursyifa; Moh Sigit Gunawan; Raden Handiriono (Indonesian Journal of Business Analytics, 2025)
A work agreement between a modeling agency and a talent model is a contract that regulates the rights and obligations of both parties. However, agencies often make mistakes, including paying the talent model late.  This study aims to examine the types of defaults that often occur in modeling agreements and the legal protection that can be provided to the model as an aggrieved party.  Using a normative juridical approach and looking at the practice of agreements and court rulings in this industry, it was found that legal protection of the model is still lacking.  This is due to poor contract clauses, poor understanding of the model, and lack of oversight from the relevant agencies. Therefore, regulations must be improved to protect the model from infringement, and fairer agreements are needed. Article 1243 of the Civil Code (Civil Code) states that the guilty party must pay the aggrieved party. Suppose the modeling agency is late in paying the talent model's salary. In that case, they are responsible for promptly paying according to the contract, paying the model's losses, paying a fine if there is a penalty clause, and facing legal consequences if the delay causes negative impacts.